2020
DOI: 10.1080/01425692.2020.1789846
|View full text |Cite
|
Sign up to set email alerts
|

The fear of being singled out: pupils’ perspectives on victimisation and bystanding in bullying situations

Abstract: The article explores 5th and 6th grade pupils' reflections on why pupils may refrain from intervening in bullying, despite understanding that bullying is wrong. The findings are based on focus group interviews conducted with 74 Swedish school pupils, who were asked for their perspectives on the various participant roles depicted in a bullying vignette. The findings were analysed using methods from constructivist grounded theory and through the theoretical lens of Goffman's concept of social stigma. The intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 52 publications
0
34
1
1
Order By: Relevance
“…Goffman (1986) suggests that 'stigma management is a general feature of society, a process occurring wherever there are identity norms' (130). Stigma processes include a number of interlinked components, including the identification of difference, labelling through the use of stigma-terms, stereotyping based on the perceived difference, isolation from those deemed 'normal', status reduction and denigration through teasing, harassment, bullying, and so on, and the subsequent maintenance of distinctions between those perceived as different and those deemed 'normal' (Link and Phelan 2001;Huggins 2016;Strindberg, Horton, and Thornberg 2020b). Just like presentations of self, stigma processes are coupled to the broader social structures underpinning them.…”
Section: School Bullying Social Power and The Presentation Of Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…Goffman (1986) suggests that 'stigma management is a general feature of society, a process occurring wherever there are identity norms' (130). Stigma processes include a number of interlinked components, including the identification of difference, labelling through the use of stigma-terms, stereotyping based on the perceived difference, isolation from those deemed 'normal', status reduction and denigration through teasing, harassment, bullying, and so on, and the subsequent maintenance of distinctions between those perceived as different and those deemed 'normal' (Link and Phelan 2001;Huggins 2016;Strindberg, Horton, and Thornberg 2020b). Just like presentations of self, stigma processes are coupled to the broader social structures underpinning them.…”
Section: School Bullying Social Power and The Presentation Of Selfmentioning
confidence: 99%
“…This response illuminates the ways in which stigmatisation can lead to social isolation through the associated risk of social contamination, and thus how the boundaries of 'us' and 'them' may be reinforced (Goffman 1986;Huggins 2016;Strindberg, Horton, and Thornberg 2020b). Social exclusion may thus not simply be about the hurtful intentions of those involved, but rather some may perceive their choice of friends to be partially out of their control: 'My friends don't let me choose for myself who I do or don't want to be friends with.…”
Section: Theme 6: Relationsmentioning
confidence: 99%
“…The stereotypes his peers had led Auggie to be labelled and even bullied. Relevant research indicates that social stigma is underpinned by factors such as labeling, discrimination and social exclusion, and that stigma can sometimes turn into bullying (Strindberg, Horton, & Thornberg, 2020;Earnshaw et al, 2018;Thornberg, 2015). From this point of view, it is important to educate individuals to reduce the destructive actions of exclusion, judgment, labeling, discrimination or even bullying caused by stigma towards people with individual differences in all kinds of social environments, especially in educational environments.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing issues of peer pressure and how these issues need to be accounted for in young people's social landscape suggests the importance of processes of social exclusion anxiety, where positions are possibly considered to be challenged when a new member comes into play (Søndergaard, 2012). Social exclusion anxiety and securing their own social position also seems to affect the ways in which they respond as bystanders (Strindberg et al, 2020). As the positions are open and fluid and attend to how implicit social power circulates (Horton, 2019;Vaillancourt et al, 2003), this might contribute to social exclusion anxiety in the group, as there are many ongoing social threats out there.…”
Section: Conclusion: School Bullying and The Ongoing Social Dynamicsmentioning
confidence: 99%
“…Those subjected to bullying may seek to avoid being positioned as a 'victim' by not disclosing what is going on (Bjereld, 2018), by reframing and distancing themselves from the incident so that they are not positioned as 'victims' (Bouchard et al, 2018) or by positioning themselves in different ways so that they can escape or overcome this position (Forsberg, 2017;Horton et al, 2015;Viala, 2015). It is commonly found that persons exposed to bullying are viewed as odd or deviant (Forsberg et al, 2014;Strindberg et al, 2020;Thornberg, 2015Thornberg, , 2018 and when becoming bystanders to bullying, different social aspects such as social hierarchies, social relations and emotions (Forsberg et al, 2014) and protecting themselves from becoming victims of bullying might affect whether young people intervene or not (Strindberg et al, 2020).…”
Section: Introductionmentioning
confidence: 99%